Biology and Control of Common Ragweed along Ditch and Canal Banks - Dennis C. Odero; Brent Sellers; Jason Ferrell (EDIS)
Common ragweed is a successful pioneer species widely distributed throughout the continental United States. In cultivated fields it will compete with crops for light, moisture, nutrients, and space and will result in significant yield losses. Additionally, allergenic airborne pollen from common ragweed is a primary cause of hay fever and thus a public health concern. This 3-page fact sheet describes the life cycle of the plant and provides management recommendations. Written by D.C. Odero, B. Sellers, and J. Ferrell, and published by the UF Department of Agronomy, April 2011.